Innovation in the Development Cooperation Framework : Case Study of Finland and Sweden - Wingström, Roosa (My University, 2019)
Science, technology and innovation are critical components of the society. In the contemporary development framework, innovation is increasingly incorporated in the development cooperation policies due to its growth-accelerating and transformative characteristics. The rapidly growing regions like Sub-Saharan Africa is undergoing substantial changes due to the fast population growth and urbanisation. The innovation-focused development policies could address these challenges and direct the region’s development path towards sustainability. In this study, I examined the role of innovation in the contemporary development framework. I first scrutinised the role of innovation in the development cooperation strategies of Finland and Sweden. I put the research in the context of Sub-Saharan Africa by examining two innovation-focused development programs, Southern Africa Innovation Support and BioInnovate Africa, supported by Finland and Sweden, respectively. Finally, I contemplated the transformative innovation framework in the context of development cooperation of Finland and Sweden, as well as the challenges and prospects of innovation-focused development. The research data of this study consisted of twelve policy/position papers related to innovation focused development cooperation as well as five interviews conducted with innovation-experts. The research data was analysed with theory-led content analysis. The research results indicate that innovation is understood as an essential part of development in the strategies of Finland and Sweden, however the approaches regarding actors and activities of innovation somewhat differ. Regional integration and improving the local innovation systems are essential objectives in the strategies. Southern Africa Innovation Support and BioInnovate Africa emphasise demand-side innovation as well as inclusive and local approach that is particularly important in the Sub-Saharan African development. The transformative innovation policy could be extremely convenient in Sub-Saharan Africa for it addresses the exclusive and resource-exhaustive tendencies of the dominant innovation path, and instead emphasises the sustainable and inclusive approaches. Further research regarding the topic is much required to comprehensively understand the mechanisms and outcomes of innovation-focused development.
Keywords: innovation, development cooperation, development policy, innovation-focused development cooperation, transformative innovation policy